BUILDING SCIENTIFIC BASIS FOR THE TERM OF “POSITIONING RESOURCES” AND PROPOSING METHODOLOGY FOR IDENTIFYING AND EVALUATING THE POSITION’S VALUE OF VIETNAM COASTAL ISLAND SYSTEMS - Thoa, Le Thi Kim (Vietnam Journal of Marine Science and Technology, 2018)
Vietnam coastal island systems play important position in socio-economic development and security, defense of the country. Among traditional resources, “position” or called as “positioning resources” is considered as a special resource. Indeed, “positioning resources” is a new term not only in Vietnam but also in other countries. As a result, this concept has always been controversy and on which full agreement in terms of scientific basis has not yet been reached. In fact, it is important to increase the understanding and awareness of coastal islands’ position, which helps to develop a new approach to evaluate the real value of these islands and to make a decision on how to utilise resonable resources. This report continues to bring out the meaning of position and its scientific basis, methodology for identifying and evaluating the position’s value of Vietnam coastal island systems